Asymmetric obligations - Nadine Riedel; Hannah Schildberg-Hörisch (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2011)
We use a laboratory experiment to investigate the behavioral effects of obligations that are not backed by binding deterrent incentives. To implement such expressive law' we introduce different levels of very weakly incentivized, symmetric and asymmetric minimum contribution levels (obligations) in a repeated public goods experiment. The results provide evidence for a weak expressive function of law: while the initial impact of high obligations on behavior is strong, it decreases over time. Asymmetric obligations are as effective as symmetric ones. Our results are compatible with the argument that expressive law affects behavior by attaching an emotional cost of disobeying the own obligation.
urn:nbn:de:bsz:100-opus-6007
Keywords: C92; H41; K40; 330; Non-binding Obligations; Expressive law; Public goods; Experiment; Soziale Norm; Normbefolgung; Öffentliches Gut; Wiederholte Spiele; Test